Pengaruh Total Aset, Dana Pihak Ketiga, Dan Pembiayaan Terhadap Keputusan Nasabah Memilih Menabung Di Bank Syariah - Ningrum, Bangun Yustia; Sartika, Nanda Lia; Agustina, Nanda; Ardana, Yudhistira (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the influence of total assets, third party funds, and financing on customer decisions in choosing to save at Bank Syariah KCP Bandar Lampung. The method used in this study is a quantitative approach with multiple linear regression analysis techniques. Data were obtained by distributing questionnaires to respondents who were customers of the bank. The results of the study indicate that simultaneously total assets, third party funds, and financing have a significant effect on customer decisions. Partially, the variables of third party funds and financing have a significant effect, while total assets do not have a significant effect. This finding indicates that factors directly related to customer service and trust in fund management are more decisive in making decisions to save at Islamic banks. Therefore, strengthening the aspects of fund collection and financing needs to be the focus of developing Islamic bank marketing strategies.